Automatic Synchronverter: Inverter Lacking a Devoted Synchronization Unit - Manoj, S; Pradeep Kumar, S; Ashok Babu, N (International Journal of Engineering and Technology, 2018)
The design of self-synchronized synchronverter is made by removing the keen synchronization unit. Synchronization with the grid takes place before connection and it will track the grid frequency after connection. Like the original synchronverter it functions in various modes to deliver the grid frequency as the reference frequency. The functions of frequency regulation, voltage regulation, real and reactive power control are maintained. Moreover, it can share the real power and reactive power accurately. Distributed energy sources delivers the major contribution to the power system operation. Generally the renewable sources are non-linear and uncontainable. Majority of renewable energy sources were associated to power systems through dc/ac converters. For this kind of application synchronizing the inverter with the grid is necessary before and after the connections to be made. It is one of the biggest challenges. So synchronverter is designed to deliver a scheme for power systems to regulate the renewable energy connected to the grid and enables smart grid integration.Â